2015
DOI: 10.1016/j.str.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

FadA5 a Thiolase from Mycobacterium tuberculosis : A Steroid-Binding Pocket Reveals the Potential for Drug Development against Tuberculosis

Abstract: Summary With the exception of HIV, tuberculosis (TB) is the leading cause of mortality among infectious diseases. The urgent need to develop new anti-tubercular drugs is apparent due to the increasing number of drug resistant Mycobacterium tuberculosis (Mtb) strains. Proteins involved in cholesterol import and metabolism have recently been discovered as potent targets against TB. FadA5, a thiolase from Mtb, is catalyzing the last step of the β-oxidation reaction of the cholesterol side-chain degradation under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 44 publications
(71 reference statements)
0
55
0
Order By: Relevance
“…In none of these instances was any CoA transferase activity detected. Finally, FadA6 shares 38% amino acid sequence identity with FadA5, a β-ketoacyl-CoA thiolase involved in cholesterol side-chain degradation (37) (Table 1), consistent with it catalyzing the thiolysis of a COCHEA-CoA ring-opened product containing a β-keto thioester moiety, to MOODA-CoA and acetyl-CoA.…”
Section: Resultsmentioning
confidence: 90%
“…In none of these instances was any CoA transferase activity detected. Finally, FadA6 shares 38% amino acid sequence identity with FadA5, a β-ketoacyl-CoA thiolase involved in cholesterol side-chain degradation (37) (Table 1), consistent with it catalyzing the thiolysis of a COCHEA-CoA ring-opened product containing a β-keto thioester moiety, to MOODA-CoA and acetyl-CoA.…”
Section: Resultsmentioning
confidence: 90%
“…Aerobic bacteria degrade steroid side chains through a series of reactions analogous to fatty acid ␤-oxidation. In M. tuberculosis, the thiolase FadA5 was proposed to catalyze the C-C bond cleavage of the side chain in the first two rounds of ␤-oxidation of the 8-carbon cholesterol side chain, releasing one molecule each of propionyl-CoA and acetyl-CoA and forming the steroid metabolite 3-OPC-CoA, with a 3-carbon side chain (11,12). In this study, we showed that cleavage of the 3-carbon side chain of this steroid metabolite during the last round of ␤-oxidation is catalyzed by an aldolase, involving Ltp2, instead of a thiolase.…”
Section: Discussionmentioning
confidence: 99%
“…The region where the glutamine and α5 would be located in degradative thiolases is hypothesized to bind fatty acyl chains. In crystal structures of degradative thiolases from S. cerevisiae and A. thaliana (PDBs 1AFW and 2WU9) [26,27], 2-methyl-2,4-pentanediol and ethylene glycol are observed in this region, and in the crystal structure of a Mycobacterium tuberculosis degradative thiolase a steroid substrate mimic can be observed (PDB 4UBT) [28]. …”
Section: Discussionmentioning
confidence: 99%